CONDITION OF IMMUNE STATUS IN ADULTS WITH ENTROBIASIS INVASION - Marchenko, V.G.; Stepanchenko, K.A. (World of Medicine and Biology, 2020)
The purpose of the present project was to study the immune status condition in patients with enterobiasis. The immune status condition was studied in 39 cadets with primary and repeated invasion with seatworms and 12 clinically healthy cadets. During the primary invasion, the immunogram indices did not differ from those of the control group and were within the reference values of the norm. The redistribution of T-helpers and T-suppressors concentrations was found during the repeated enterobiasis with a marked decrease in the level of immunoregulatory cells possessing the T-helper activity, which is, in our opinion, a significant factor leading to the development of stable immunocomprometation and may further lead to reinvasion. Changes in the macrophage-phagocytic system indicate a decrease in the killing effect of phagocytic neutrophils in the peripheral blood against the background of their compensatory stress during repeated enterobiasis invasions.
Keywords: enterobiasis; seatworms; reinvasion; immune status; adults